2015
DOI: 10.1002/eat.22471
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and choroidal alterations in patients with anorexia nervosa without vision loss

Abstract: In AN patients, even without vision loss, significant changes occur in retinal and choroidal thickness, as well as in the electrical activity of the macula. However, this is a pilot study in a small sample that needs replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Only two studies evaluating ERG in the context of eating disorders met our inclusion criteria [58, 59]. Nasser et al [58] discussed oral food stimulation in the setting of binge eating, while the study by Moschos et al [59] discussed anorexia nervosa.…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies evaluating ERG in the context of eating disorders met our inclusion criteria [58, 59]. Nasser et al [58] discussed oral food stimulation in the setting of binge eating, while the study by Moschos et al [59] discussed anorexia nervosa.…”
Section: Resultsmentioning
confidence: 99%
“…No significant difference was found in the two studies in patients with Major depressive disorder [17,18]. In another study with 13 women with Anorexia nervosa, the macular thickness was found to be decreased in anorexia cases, while no difference was found in RNFL thickness between groups [19].…”
Section: Discussionmentioning
confidence: 85%
“…As a result of a meta-analysis of case-control studies related to this issue and performed in 2018, it was stated that RNFL can be used as a diagnostic tool in schizophrenia [16]. In addition to studies about schizophrenia, there are researches that ocular findings have been evaluated by using OCT in patients with Major depressive disorder, ADHD and Anorexia nervosa [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…These findings were also found to be related to BMI at presentation and duration of disease, RNFL thickness being negatively correlated to both. 102 In addition, patients with different subtypes of AN, namely restrictive AN and purge type AN, exhibited differences in overall retinal thickness of the macula, values being higher in the restrictive type which indicates that the anatomical impairment of the fovea maybe greater in the purge type AN. These findings suggest that OCT can help us understand the pathophysiology and ocular effects of AN, a subject that is currently poorly understood.…”
Section: Review Of Diseasesmentioning
confidence: 98%